A Facile Linking of the Pyrrole Ring with Functionalized 3(2H)-Furanone Moieties - Malkina, Anastasiya G.; Shemyakina, Olesya A.; Stepanov, Anton V.; Volostnykh, Olga G.; Ushakov, Igor A.; Sobenina, Lyubov N.; Borodina, Tatyana N.; Smirnov, Vladimir I.; Trofimov, Boris A. (Synthesis, 2016)
The CN-functionalized pyrrole(indole)-3(2H)-furanone derivatives are readily synthesized via the domino reaction of diverse pyrrole(indole) carboxylic acids with tertiary cyanopropargylic alcohols (Et3N, MeCN, MW reactor, 100 °C, 1.2 atm) in up to 93% yield.
Keywords: pyrrole(indole)-2-carboxylic acids; tertiary cyanopropargylic alcohols; domino reaction; cyclization; pyrrole(indole)-3(2H)-furanone derivatives